INTERNALISASI PEDULI LINGKUNGAN PADA PESERTA DIDIK MELALUI PEMBELAJARAN BERBASIS LINGKUNGAN - Adya Pribadi, Reksa; Ayu Faradiba, Salsa; Delia Noventy, Citta (STKIP Subang, 2021)
Formal education is generally more concerned with intellectual development. Therefore, there are still many schools that have not optimally paid attention to the character of students, one of which is the character of caring for the environment which is currently a community need in the midst of the crisis of environmental destruction. The research that will be conducted is research with a qualitative approach, descriptive method. This study aims to find out how the internalization of environmental care for students through environment-based learning at SDN Cikokol 1. Data collection techniques use observations and interviews. The results showed that the internalization of environmental care through environment-based learning at SDN Cikokol 1 had been carried out well, it could be said that the students' understanding and awareness of environmental sustainability and existing environmental conditions had increased. Based on the results of research and discussion, it can be concluded how to overcome environmental problems in the future, namely by providing education about the environment from an early age through elementary schools.